Organizational Transformation Through Business Innovation and Disruptive Technology: Value-Based Leadership in Shaping a Dynamic and Adaptive Organizational Culture - Saranani, Fajar; Ausat, Abu Muna Almaududi; Rijal, Syamsu (ADMAN: Journal of Contemporary Administration and Management, 2024)
In an era of globalization and rapid technological advancement, changes in the business landscape are becoming increasingly fast-paced and unpredictable. Companies must be able to adapt quickly to remain competitive and thrive. The aim of this research is focused on how companies can integrate business innovation and disruptive technology, as well as how value-based leadership can shape a dynamic and adaptive organizational culture to tackle the challenges of transformation in the ever-changing business landscape. This research method is a literature review with a qualitative approach, focusing on descriptive analysis. The data used in this study are from scholarly articles found through Google Scholar, with a publication range from 2001 to 2023. The study findings indicate that in the dynamic and fast-paced modern era, organizational transformation is key to maintaining relevance and competitiveness. This transformation involves the adoption of business innovation, the implementation of disruptive technology, and the development of value-based leadership. By combining these three aspects, an organization can create a dynamic and adaptive environment, where change is seen as an opportunity for growth.